Shifting from quinine to artesunate as first-line treatment of severe malaria in children and adults: Saving more lives - Jean Jacques N. Noubiap (Elsevier, 2014)
Summary: Severe malaria kills more than a half million people each year. Based on high-quality evidence of the efficacy superiority of artesunate over quinine in adults and children with severe malaria, the World Health Organization guidelines have been revised. The WHO currently recommends injectable artesunate as the first-line treatment for severe malaria. Since this revision in April 2011, only a small number of countries affected by malaria have adopted and implemented the new policy. If this policy is implemented, an additional 195,000 lives would be saved each year in Africa. Thus, there is an urgent need to speed up access to injectable artesunate in malaria-endemic countries. This review presents a background for recommending artesunate as the first-line treatment of severe malaria in children and adults, and interventions that are recommended to accelerate access to injectable artesunate. Keywords: Severe malaria, Artesunate, Quinine